Enhancing mechanical strength and tribological performance in tin bronze alloys via rolling treatment - Wen Zhong; Liang Wang; Dun Miao; Xiang Cai; Mengmeng Yang; Yanxin Qiao; Qichao Zhang; Jian Zhou (npj Materials Degradation)
Abstract This study electroplates a 2 μm thick Al layer on mild steel, then uses wire-arc directed energy deposition (DED) to deposit Cu-4.2Sn alloy, forming a composite material which is subsequently cold-rolled. It investigates the microstructure, mechanical properties, and tribological behavior before and after rolling, along with underlying mechanisms. It indicates that Al coating completely suppresses penetration cracks on the steel side of the tin bronze/steel bimetal. After rolling, tin bronze grains are significantly refined (from 47.6 μm to 15.2 μm) with numerous twins formed, reducing matrix dislocation density. Compared to wire-arc DED alloy, rolled alloy hardness increases by 78%, yield strength by 51%, and tensile strength by 30%. Tribological tests indicate, under dry friction and simulated seawater conditions, the rolled alloy’s coefficient of friction (COF) and mass loss decrease by 30% and 24% respectively. Analysis of corrosion-friction synergy reveals interaction loss accounts for 13%, dominated by friction-promoted corrosion (11%).